EFFECTIVENESS OF ZINC SUPPLEMENTATION FOR TYPE II DIABETES PREVENTION: A SYSTEMATIC REVIEW: EFEKTIVITAS SUPLEMENTASI ZINK UNTUK PENCEGAHAN DIABETES TIPE II: TINJAUAN SISTEMATIS - Ridwan, Alifaturrasyid Syafaatullah; Suryoadji, Kemal Akbar; Rycko, Nada Salsabila; Wisnu, Wismandari (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2022)
Background: The incidence of prediabetes is predicted to continue to increase. Approximately 25% of prediabetes patients develop type 2 diabetes mellitus (T2DM) within 3–5 years. Zinc is known to have a role in the synthesis, storage, secretion, and action of the insulin hormone. Purpose: The aim of the study is to know about the impact of zinc supplementation in type 2 diabetes mellitus (DM) prevention. Methods: A systematic literature search was performed using the PubMed, Cochrane, and EBSCOHost search engines. The inclusion study includes systematic review and metaanalysis of randomized clinical trials study and randomized clinical study, and we only include the research of the last 10 years. Results: Three RCTs were selected from 175 articles to undergo a critical review with a total of 353 patients with a duration of 6-12 months (level of evidence II-III). The incidence of T2DM in the intervention group decreased significantly (OR: 0.37 [95% CI 0.7-0.8]; RR: 0.44; ARR: 14% [95% CI 3.5-24.5%]; NNT: 7.14 [4-29]) in one study. Zinc supplementation significantly reduced Fasting Blood Sugar (FBS) in two studies (mean difference -17.3 and -5.76) and oral glucose tolerance test (OGTT) in one study (MD -22.6). Conclusion: Administration of zinc in prediabetes patients to prevent the development of T2DM still requires further study with a larger sample, longer duration, and control variables by design and statistics.